Reduced enzyme activity following Hsp70 overexpression in Drosophila melanogaster. - Krebs, R.A.; Holbrook, S.H. (Biochemical Genetics, 2001)
Acclimation to environmental change can impose costs to organisms. One potential cost is the change in cell metabolism that follows a physiological response, e.g., high expression of heat shock proteins may alter specific activity of important enzymes. We examined the significance of this cost in a pair of Drosophila melanogaster lines transformed with additional copies of a gene that encodes the heat shock protein, Hsp70. Heat shock induces Hsp70 expression in all lines, but lines with extra copies produce much more Hsp70 than do excision control strains. The consequence of this supranormal Hsp70 expression is to reduce specific activity of both enzymes analyzed, adult alcohol dehydrogenase (ADH), which is heat sensitive, and lactate dehydrogenase, which is not. Strain differences were most pronounced under those conditions where Hsp70 expression was maximized, and not where the heat stress denatured proteins. That result supported the idea that Hsp70 expression is constrained evolutionarily by its tendency to bind nascent peptides when overabundant within the cell.